2018
DOI: 10.21283/2376905x.9.165
|View full text |Cite
|
Sign up to set email alerts
|

Reseña: García, Ofelia, Ibarra Johnson, Susanna, & Seltzer, Kate (2017). The translanguaging classroom: Leveraging student bilingualism for learning. Philadelphia, Pennsylvania: Caslon.

Abstract: En la última década, hemos presenciado un giro plurilingüe en la educación que ha suscitado un creciente interés por la adopción de pedagogías centradas en la interacción entre lenguas y la naturalización de las prácticas lingüísticas de los estudiantes bi/multilingües (p. ej., Corcoll, 2013;Colina & Lafford, 2017;González Davies, 2014, 2018). Estas pedagogías responden a la nueva conceptualización de que los repertorios lingüísticos de los aprendientes están interconectados, en oposición a la perspectiva mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…However, further research and teacher training are needed to better support teachers to incorporate students' multilingual repertories in the mathematics classroom. Including the language-as-resource perspective and intuitive translanguaging (García et al, 2017) may have the potential to support the migrant students to rather use their language skills for sense making and mathematical discussions instead of restricting it. In recent years, some ideas for curriculum design and practice in STEM multilingual contexts have been published (see Essien & Msimanga, 2021).…”
Section: Discussion Limitations and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further research and teacher training are needed to better support teachers to incorporate students' multilingual repertories in the mathematics classroom. Including the language-as-resource perspective and intuitive translanguaging (García et al, 2017) may have the potential to support the migrant students to rather use their language skills for sense making and mathematical discussions instead of restricting it. In recent years, some ideas for curriculum design and practice in STEM multilingual contexts have been published (see Essien & Msimanga, 2021).…”
Section: Discussion Limitations and Concluding Remarksmentioning
confidence: 99%
“…This notion refers to the fluid and often deliberate interweaving of repertoires of more than one language in educational contexts. It has become widely adopted in second language education, bilingual education, and other educational contexts featuring language diversity (see García et al, 2017). In mathematics classrooms, multilingual learners may display translanguaging behaviors with a repertoire of multiple languages.…”
Section: Theoretical Framework and State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 10 years, translanguaging theory and pedagogies have flourished, and they have been immensely helpful in showing the rigorous, advanced and creative linguistic practices of bilingual youth in the United States, as well as elsewhere in the world (García et al., 2017; García-Mateus and Palmer, 2017). This is especially significant, given that racialized bilingual youth are often construed as deficit and lacking in US educational discourses of assessment and school achievement (Flores and Rosa, 2015).…”
Section: Theoretically Unframing a Research Projectmentioning
confidence: 99%
“…In schools, scholarship has shown that translanguaging pedagogies leverage the entire linguistic repertoire of students for classroom learning (García et al., 2017). In turn, translanguaging pedagogies and practices have been shown to have an inherent resistance embedded in them (Prada and Nikula, 2018).…”
Section: Theoretically Unframing a Research Projectmentioning
confidence: 99%